Sympathetic Overactivation From Supine to Upright Is Associated With Orthostatic Hypertension in Children and Adolescents - Hu, Yang; Wang, Yuanyuan; He, Bing; Wang, Yaru; Han, Zhenhui; Tao, Chunyan; Li, Hongxia; Jiang, Yi; Tang, Chaoshu; Du, Junbao (Frontiers in Pediatrics, 2020)
.Objectives: The study was conducted to analyze the changes of baroreflex sensitivity and heart rate variability from supine to upright standing in children and adolescents with orthostatic hypertension to explore whether and how the autonomic nerve regulation was involved in the development of pediatric orthostatic hypertension. Methods: This case-control study included twenty-five children with orthostatic hypertension (the patient group) and twenty-six healthy controls (the control group). All subjects underwent a standing test, during which their hemodynamic parameters were continuously monitored by a Finapres Medical System, and baroreflex sensitivity and heart rate variability were calculated. Results: The demographic characteristics, supine baroreflex sensitivity and supine heart rate variability including time domain and frequency domain indices did not differ between the patients with orthostatic hypertension and healthy subjects (P > 0.05). However, a more obvious drop of baroreflex sensitivity and a greater increase of low frequency / high frequency ratio from supine to upright were observed in subjects with orthostatic hypertension compared with those in the healthy children (P < 0.001 and P < 0.01, respectively). Changes of baroreflex sensitivity were negatively related to mean arterial pressure changes from supine to upright in all subjects (P < 0.01), and the increases in low frequency / high frequency ratio from supine to standing were positively correlated with those in mean arterial pressure in the study subjects (P < 0.001). Conclusion: Upright sympathetic overactivation is associated with pediatric orthostatic hypertension.